Effect of Long-Term Immersion on the Corrosion and Passivation Behavior of Lean Duplex Stainless Steel 2101 in 3.5 wt% NaCl Solution - Bairi, Lipika Rani; Bairagi, Darothi; Duley, Partha; Mandal, Sumantra (Metals and materials international, 2023)
The current study investigates the effect of long-term immersion on the corrosion response and the consequent passive film formation process of lean duplex stainless steel 2101 in 3.5 wt% NaCl solution. The corrosion behavior of the alloy has been monitored through long term immersion tests at different time intervals, viz . 0, 3, 5, 10, 20, 40, and 70 days. The electrochemical tests, such as potentiodynamic polarization and electrochemical impedance spectroscopy, have been performed after each immersion period to understand the change in corrosion rate and passivation behaviour, respectively, with respect to immersion duration. With the increase in immersion duration, the pitting potential ( E pit ) gradually shifts towards a nobler direction with a simultaneous reduction in corrosion rate ( r corr ). This has been attributed to the gradual increase in the thickness of the passive film with the increase in duration of immersion, as revealed through the EIS analysis. The passive film is found to become nearly stable after 40 days of immersion of the specimen in 3.5 wt% NaCl solution. Interestingly, the thickness and stability of the passive film obtained after 40 days of immersion in 3.5 wt% NaCl solution are comparable to the passive film that is formed in mildly passivating media, namely borate buffer solution. An investigation of post immersion surface morphology has also confirmed the gradual improvement in the uniformity and compactness of the oxide-rich passive layer with increase in immersion period, which eventually led to improved corrosion resistance of the alloy in the saline environment. Graphical Abstract